2013
DOI: 10.1002/ajmg.a.36233
|View full text |Cite
|
Sign up to set email alerts
|

X chromosome exome sequencing reveals a novel ALG13 mutation in a nonsyndromic intellectual disability family with multiple affected male siblings

Abstract: X-linked intellectual disability (XLID) is a heterogeneous condition associated with mutations in >100 genes, accounting for over 10% of all cases of intellectual impairment. The majority of XLID cases show nonsyndromic forms (NSXLID), in which intellectual disability is the sole clinically consistent manifestation. Here we performed X chromosome exome (X-exome) sequencing to identify the causative mutation in an NSXLID family with four affected male siblings and five unaffected female siblings. The X-exome se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…Similar cases of males with ALG13 mutations transmitted from their unaffected mothers have been reported. 20 We therefore considered this variant, which was predicted to have altered splicing, to be possibly causative.…”
Section: Resultsmentioning
confidence: 99%
“…Similar cases of males with ALG13 mutations transmitted from their unaffected mothers have been reported. 20 We therefore considered this variant, which was predicted to have altered splicing, to be possibly causative.…”
Section: Resultsmentioning
confidence: 99%
“…Transferrin isoelectric focusing showed increased asialo-and disialotransferrin fractions. Two other missense mutations were found in four brothers affected with intellectual disability and in a male patient with ISs and optic nerve atrophy (15,16). 10A1280 was the only patient with the p.Asn107Ser in whom transferrin glycosylation was assayed.…”
Section: Discussionmentioning
confidence: 99%
“…To date, this is the only CDG reported due to a variant in ALG13. Bissar-Tadmouri et al (2014) identified a novel missense variant, 3221A>G in ALG13 (p.Y1074C), that segregated with a non-syndromic X-linked intellectual disability disorder family with four affected boys. No additional clinical information was provided in the report.…”
Section: Introductionmentioning
confidence: 99%